Economic modelling to evaluate Smart Specialisation: an analysis of research and innovation targets in Southern Europe. Issue 9 (2nd September 2022) - Barbero, Javier; Diukanova, Olga; Gianelle, Carlo; Salotti, Simone; Santoalha, Artur
ABSTRACT: We make the case for a technology-enabled approach to Smart Specialisation policymaking aimed at increasing its effectiveness by assessing the general equilibrium effects of the European Cohesion Policy objectives contained in the regional Operational Programmes prepared by the regional policymakers. We simulate the impact of achieving the research and development personnel targets on gross domestic product and its components in a set of Southern European regions. We discuss the implications and challenges of the proposed methodology for future assessments of Smart Specialisation and for its implementation in the regions of the European Union.